In vitro culture of the moss Hyophilla nymaniana (Fleish.) Menzel and its phytochemical screening - Rashmi Mishra; Vijay Kant Pandey; Ramesh Chandra (International Journal of Phytomedicine, 2014)
Bryophytes are the second largest group of land plants after angiosperm and are considered as a remarkable reservoir of many new, natural products or secondary metabolites, which have shown interesting biological activity. The full economical potential of bryophytes is not completely explored. The present study aims to establish an efficient protocol for in vitro culture of one of the species of moss Hyophilla nymaniana (Fleish.) Menzel and to perform phytochemical screening of this moss. Media content as well as light and temperature were varied to get the optimum condition for spore germination. Maximum number of spore germinated in 1/4 strength MS containing 1.5% sucrose and 2% of NaOCl was found to be the best for surface disinfection of sporophyte. Temperature range of 22±1 ͦC and pH 6 along with light intensity of 2000-4000 lux with alternate day and night condition of (16/8 hours) was found suitable for the growth of the plant. For phyotochemical screening the methanolic ethanolic and ethyl acetate extract of the moss prepared. Ethanolic extract showed the presence of alkaloids, glycosides, steroids and terpenoids.